Risk-return analysis : the theory and practice of rational investing vol. 1 - Markowitz, Harry; Blay, Kenneth (New York : McGraw-Hill Education, 2014)
The Nobel Prize-winning Father of Modern Portfolio Theory provides new insights and methods to help you build a lasting portfolio.
Includes bibliographical references (pages 209-215) and index.
rpm 24/10/2017
Loans
Keywords: Investment analysis; Investments--Mathematical models; Portfolio management